Analysis of Electronic Medical Record Reception using Expanded Technology Acceptance Model - Indra Kharisma Raharjana; Faisal Apriyana; Taufik Taufik (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
Information technology in the health sector has the potential to increase the quality of patient care by improving process efficiency, reducing errors and reducing costs. But this potential cannot be achieved if there is rejection from stakeholders. In this study, we examine the information technology acceptance model in the medical field. We use Moores's model that was developed from Davis's Technology Acceptance Model by adding the variables that determine the success of information technology acceptance. The variables are divided into two categories: information quality consisting of accuracy, content, timeliness, and format. The Enabling factors consisting technical support and self-efficacy. The case study was conducted among medical personnel at a Hospital in East Java. The subject of research is the use of the electronic medical record. Data were obtained through a questionnaire. Then the data is processed with Partial Least Squares algorithm using PLS software. As a result of the sixteen hypotheses proposed there are fourteen hypotheses accepted and the overall model deemed appropriate.